Effects of Manganese on (p)ppGpp Homeostasis in Bacillus subtilis - Kaufmann, Adam (My University, 2018)
The bacterial nucleotide signal (p )ppGpp is an important signal for stress survival, antibiotic tolerance, and virulence in common pathogens. In addition, the group 7 metal manganese has been implicated in having critical roles in proper cell function and physiology, as well as essential for virulence. However, the potential interactions between the two virulence drivers are unclear. Here we tested the potential role of cellular manganese in effecting (p)ppGpp levels in Bacillus subtilis. Using a set of Mn uptake mutants and metal starvation conditions, we found that Mn imbalanee in the eell can influence cellular (p )ppGpp. Though the exact mechanism has yet to lie elucidated. We demonstrate that intracellular Mn2+ imbalance can be another signal that may influence (p)ppGpp homeostasis and antibiotic tolerance.